Course Review: Ichnology (Trace Fossils) Course - Mariana Omar (Ikatan Ahli Geologi Indonesia, 2004)
Course Review: Ichnology (Trace Fossils) CourseBrunei Shell Petroleum, Seria (29th September-1st October 2003)By: S. George Pemberton (University of Alberta, Canada)